Energy and environmental challenges in Central Asia and the caucasus - "Soni,Preeti. (ed.)" (New Delhi, 1996)
With the collapse of the FSU (former Soviet Union) in 1991, several new independent republics appeared on the world map. These include Kazakhstan, Kyrgyzstan, Tajikistan Turkmenistan, and Uzbekistan in Central Asia, and Armenia, Azerbaijan, and Georgia in the Caucasus. While the political developments have posted numerous challenges for these republics, they have also opened enormous oppurtunities for them to look beyond FSU, and develop economic and commercial relations with other countries.
Keywords: Energy